A Study on Organisational Climate, Job Satisfaction and Workload Perception of Forestry Extension Personnel in Tamil Nadu - Irulandi, V.; Ranganathan, T. T.; Ramasubramanian, M. (Indian Forester, 2015)
A study was conducted among sixty six forestry extension personnel of Forest Department of Tamil Nadu to assess the organsational climate, workload perception and job satisfaction. The findings revealed that 48.48 per cent of the respondents were found to be in the medium category of guidance and supervision, Respondents were distributed equally between low (34.85 per cent), medium (33.33 per cent) and high (31.82 per cent) categories for facilities and resources component of organizational climate. An appreciable number of respondents were also found to possess low to medium team work perception. Majority of forestry extension officials perceived the workload related to field work, conducting demonstrations, trainings, campaigns, making the farmers participate as heavy to moderately heavy. Inadequate skill, inadequate staff strength, transfer policy, inadequate time and poor research-extension linkagewere found to influence job satisfaction as majority of officials reported to agree with these factors. The correlation and regression analyses revealed that there existed strong relationship between job satisfaction, workload perception and organisational climate and they contributed to each other immensely. In line with the findings of the study, suitable strategies to strengthen the forestry extension wing were suggested.